Corporate Activism and Employee Retention in a Selected Multinational Corporation in Shandong City, China - Wang, Jie (Pacific International Journal, 2025)
This study examines the relationship between corporate activism and employee retention in a multinational corporation in Shandong, China, using a quantitative comparative correlational design with 300 employees. Findings reveal high levels of corporate activism across shareholder engagement with a mean of 2.89, sociopolitical involvement at 2.86, sustainability initiatives at 2.90, and reputation strategy at 2.74. Sociopolitical activism showed the strongest positive correlation with job satisfaction at 0.42. Employee retention metrics were consistently high with an overall mean of 2.87, though significant gender differences emerged, with male employees reporting 12% higher job satisfaction and 9% more favorable leadership perceptions than females. Mid-level employees demonstrated 15% stronger career development perceptions compared to other levels, while work-life balance satisfaction dropped 18% among employees with 7-10 years of service. The study identifies three key mechanisms through which corporate activism influences retention: value alignment at 0.38, leadership credibility at 0.29, and organizational transparency at 0.25. These findings suggest that while corporate activism generally enhances retention, its impact varies across demographic groups, recommending tailored communication strategies and leadership development programs to maximize retention benefits across all employee segments.